1994
DOI: 10.1523/jneurosci.14-10-05834.1994
|View full text |Cite
|
Sign up to set email alerts
|

Sodium/calcium exchange in rat cortical astrocytes

Abstract: Regulation of the cytosolic free Ca2+ concentration ([Ca2+]cyt) by an Na/Ca exchanger was studied in primary cultured rat cortical astrocytes. [Ca2+]cyt was measured by digital imaging in cells loaded with fura-2. The resting [Ca2+]cyt, approximately 150 nM, was only slightly increased by reducing the extracellular Na+ concentration ([Na+]o) to 6.2 mM, or by treating the cells with ouabain for 15 min (to raise cytosolic Na+). Following treatment with ouabain, however, lowering [Na+]o caused [Ca2+]cyt to rise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 47 publications
(53 reference statements)
8
79
0
Order By: Relevance
“…The source of Ca 2ϩ that permits these changes can be either intracellular, i.e., release from stores, and/or extracellular, i.e., entry through plasma membrane channels and ion exchangers. Although a contribution of the Na ϩ and Ca 2ϩ exchanger cannot be excluded (Goldman et al, 1994), our results suggest that the release of Ca 2ϩ from intracellular Ca 2ϩ stores and the Ca 2ϩ release-activated Ca 2ϩ influx are major mechanisms used by astrocytes to achieve rises in their [Ca 2ϩ ] i that could have functional significance for the triggering of Ca 2ϩ -dependent events.…”
Section: Discussionmentioning
confidence: 72%
“…The source of Ca 2ϩ that permits these changes can be either intracellular, i.e., release from stores, and/or extracellular, i.e., entry through plasma membrane channels and ion exchangers. Although a contribution of the Na ϩ and Ca 2ϩ exchanger cannot be excluded (Goldman et al, 1994), our results suggest that the release of Ca 2ϩ from intracellular Ca 2ϩ stores and the Ca 2ϩ release-activated Ca 2ϩ influx are major mechanisms used by astrocytes to achieve rises in their [Ca 2ϩ ] i that could have functional significance for the triggering of Ca 2ϩ -dependent events.…”
Section: Discussionmentioning
confidence: 72%
“…The location of the high affinity isoforms appears to provide a clue because the SR and ER sequester Ca 2ϩ , and the Ca 2ϩ released from these organelles controls numerous cell activities. A critical link between the Na ϩ pump and cell Ca 2ϩ is the PM Na ϩ ͞Ca 2ϩ exchanger, which is also localized to PM regions that overlie junctional SR and ER (11,14,15,31). The energy required to control cytosolic Ca 2ϩ via the Na ϩ ͞Ca 2ϩ exchanger is derived from the Na ϩ electrochemical gradient generated by the Na ϩ pump (12).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that inhibition of NCX can result in increased Ca 2ϩ concentrations in other cells, including glial cells (39). In olfactory bulb astrocytes, this increase in the cytosolic Ca 2ϩ concentration depended on extracellular Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 97%